Evaluation of a nursing student health fair program: Meeting curricular standards and improving community members' health. Issue 5 (17th April 2018) - Salerno, John P.; McEwing, Evan; Matsuda, Yui; Gonzalez‐Guarda, Rosa M.; Ogunrinde, Olutola; Azaiza, Mona; Williams, Jessica R.
Abstract: Background: Public health nursing (PHN) is an essential component of baccalaureate nursing education. In order to build PHN competencies, universities must design and operationalize meaningful clinical activities addressing community and population health. Currently, there is a paucity of literature delineating best practices for promoting competency in PHN. Aims: The purpose of this manuscript is to describe a PHN‐student health fair program as a means for meeting undergraduate PHN curricular standards, and to report results of an evaluation conducted examining its effectiveness in improving community member's health knowledge. Methods: Health fairs were held at community agencies that served the homeless or victims of intimate partner violence. A total of 113 community members that attended a health fair were assessed at baseline and immediate posttest using open‐ended questionnaires. The design of the health fairs included a community assessment, intervention, and evaluation flow that followed the nursing process. Results: We report that results from participants surveyed indicated that PHN‐student delivered health fairs improved health knowledge among community members in this sample ( p = .000). Conclusion: Health fairs conducted by PHN students appear to be promising community health promotion and disease prevention interventions that can serve as an effective strategy for teaching PHN student competencies and facilitating engagement with the community.